(untitled) (Materiali di Estetica. Terza serie, 2017)
In our metaphysical tradition, art has always been intended as the opposite pole of nature. Art, in the strict philosophical meaning of the concept, has always indicated the artificial character of a thing. In this sense, art has been intended as the name of the process through which an artificial object is produced. For this reason, the Greek term for art is téchne, which also means technology. But art also means the artistic, aesthetic character of things, particularly of natural things. That is why it is imperative to reconsider the philosophical meaning of art, nature, technology and their problematic conceptual relationship.